Increased ion transport and high-efficient osmotic energy conversion through aqueous stable graphitic carbon nitride/cellulose nanofiber composite membrane. (15th March 2022) - Gao, Zongxia; Sun, Zhe; Ahmad, Mehraj; Liu, Yuqian; Wei, Haiying; Wang, Sha; Jin, Yongcan
Abstract: Increased attention has evoked on the utilization of renewable energy, particularly osmotic power as a potential solution to the energy crisis and environmental pollution. Herein, we fabricate graphitic carbon nitride (g-C3 N4 )/cellulose nanofiber (CNF) composite membranes with tailored lamellar nanochannels for capturing osmotic energy from salinity gradients. Composite membranes exhibiting charge-governed ion conductivity were prepared via co-homogenization of g-C3 N4 with CNF and vacuum filtration. Ion conductivity was efficiently modulated by fine-tuning the charge density through controlling the weight content of CNF in the composite membranes. Higher ion conductivity of 0.014 S cm −1 at low concentrations (<10 −2  M KCl) was achieved due to the increased charge density of the lamellar nanochannels and the excellent aqueous stability of the membranes. We demonstrate the potential of the composite membranes in nanofluidic osmotic energy conversion, displaying thermo-enhanced power output performance. This work could inspire new designs of cellulose-based nanofluidic devices for improved osmotic energy conversion. Graphical abstract: Unlabelled Image